Health-related quality of life in patients with anal fissure: effect of type D personality - Sit, Mustafa; Yilmaz, Edip Erdal; Canan, Fatih; Yildirim, Osman; Cetin, Mehmet Mustafa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Health-related quality of life (HRQL) is a significant factor in describing the burden of illness and the impact of treatment in patients with gastrointestinal disease. Type D (distressed) personality is defined as the co-occurrence of negative affect and social inhibition. Aim : To assess the prevalence of type D personality in patients with anal fissure and to investigate whether the presence of a type D personality would affect HRQL in patients with anal fissure. Material and methods : One hundred outpatients with anal fissure with no psychiatric comorbidity were consecutively enrolled, along with 100 healthy controls. Type D Scale (DS14) and General Health Survey Short Form-36 (SF-36) were used in the collection of data. Results: Patients with anal fissure scored lower on physical roles and bodily pain dimensions of SF-36 than healthy subjects (p < 0.05). Thirty-three patients with anal fissure (33%) and 16 controls (16%) had scored above the cut-off score of the DS14 (p < 0.05). Patients with a type D personality were found to score lower on bodily pain and social roles domains of HRQL than patients without a type D personality. Conclusions: Type D personality was associated with increased perceived bodily pain and social roles in patients with anal fissure. Type D personality construct may be an important consideration when assessing HRQL outcomes. A multidimensional approach may be valuable in the assessment of patients presenting with anal fissure, because a subgroup with type-D personality might benefit from psychological therapies.